2013
DOI: 10.1158/1541-7786.mcr-12-0593
|View full text |Cite
|
Sign up to set email alerts
|

RAS/MEK–Independent Gene Expression Reveals BMP2-Related Malignant Phenotypes in the Nf1-Deficient MPNST

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is a type of soft tissue sarcoma that occurs in carriers of germline mutations in Nf1 gene as well as sporadically. Neurofibromin, encoded by the Nf1 gene, functions as a GTPase-activating protein (GAP) whose mutation leads to activation of wt-RAS and mitogen-activated protein kinase (MAPK) signaling in neurofibromatosis type I (NF1) patients' tumors. However, therapeutic targeting of RAS and MAPK have had limited success in this disease. In this study, we modula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…A recent in vitro study confirmed our original finding that MAF expression is low in ST88-14 NF1 mutant MPNST cells relative to normal human Schwann cells (24), and that SOX9 is elevated (41). MAF expression is also reduced in prostate cancer (42).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A recent in vitro study confirmed our original finding that MAF expression is low in ST88-14 NF1 mutant MPNST cells relative to normal human Schwann cells (24), and that SOX9 is elevated (41). MAF expression is also reduced in prostate cancer (42).…”
Section: Discussionsupporting
confidence: 67%
“…MAF expression is also reduced in prostate cancer (42). We found that levels of MAF are very low in all tested MPNST cell lines, including sporadic MPNST cells (24), possibly accounting for the fact that siRNA targeting NF1 in a sporadic (non-NF1 mutant) MPNST cell line did not alter MAF expression (41). Our finding that the NF1-GRD regulates MAF expression implies that activation of one or more Ras proteins suppresses MAF .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Human NF1-associated MPNST cell lines NF90.8 and ST88-14 were provided by Dr Michael Tainsky (Wayne University, Detroit, MI), T265-2C was obtained from Dr Steven Porcelli (Albert Einstein College of Medicine, Bronx, NY), and sNF96.2 was purchased from ATCC (Manassas, VA) [15, 16]. MPNST cells were maintained in RPMI 1640 medium (Sigma) containing 10% of fetal bovine serum (BenchMarck, Gemini Bio-Products, West Sacramento, CA) and 1% penicillin- streptomycin (Invitrogen Life Technologies, Carlsbad, CA) at 37°C in an humidified 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Neurofibromatosis type 1 disease (NF1; Online Mendelian Inheritance in Man/OMIM—database #162200) is a rare chronic neurological disorder caused by a deficient autosomal dominant genetic background, which affects 1 in 3000 live births [1]. Alterations in the tumor suppressor gene neurofibromin (NF1) enhance expression of the Ras signaling pathway, which is involved in the evolution of many cancers [2].…”
Section: Introductionmentioning
confidence: 99%